Edukasi Dan Pendampingan Pembuatan Rebusan Jahe Untuk Menurunkan Tekanan Darah Pada Lansia Penderita Hipertensi - Adhin Al Kasanah; Achmad Vindo Galaresa; Kartika Kartika (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Hypertension is a disease whose prevalence continues to increase every year. Uncontrolled hypertension can cause various complications, so comprehensive management is needed to treat this disease. One non-pharmacological therapy for treating hypertension is ginger. Ginger contains flavonoids which can have a vasodilation effect so scientifically it can lower blood pressure. The method used in this service is a lecture and simulation of making ginger stew to lower blood pressure. The results of blood pressure examinations showed that 71% of participants had hypertension. The knowledge value before providing education and simulating making ginger stew was 64.5, while the value after providing education and simulating making ginger stew was 84.2.